Report of the Working Group on Environment and Environmental Regulatory Mechanisms in Environment & Forests for the Eleventh Five Year Plan (2007-2012) - Planning Commission (Planning Commission, 2007)
The Ministry of Environment and Forests is primarily concerned with the implementation of policies and programmes relating to conservation of the country’s natural resources including lakes and rivers, its bio-diversity, forests and wildlife, ensuring the welfare of animals and prevention and abatement of pollution.
Government of India Planning Commission
Government of India Planning Commission